Superpower by invitation: late Cold War diplomacy and leveraging Armenian terrorism as a means to rapprochement in Israeli-Turkish relations (1980–1987). Issue 2 (3rd April 2019) - Ben Aharon, Eldad
ABSTRACT: This article puts forth the argument that Israel's desire to repair its deteriorating relations with Turkey between 1980 and 1985 drove Israeli diplomats to leverage Armenian terrorism as an issue of shared concern with Turkey. Specifically, the Armenian Secret Army for the Liberation of Armenia (hereafter, ASALA), apparent affiliation with a similar brand of Palestinian terrorism, which was supported by the Soviet Union, was used to court Turkey. This overlooked factor also provides a template with which to understand Israel's policy on the contested memories of the Armenian Genocide during the 1980s. In the context of a late Cold War superpower rivalry, this article demonstrates how Israeli diplomats assigned the US to mediate between Ankara and Jerusalem. This context highlights the degree to which Cold War dynamics were two-sided: how regional powers such as Israel attempted to influence the policies of the superpower US in the later Cold War years through leveraging global terrorism for diplomatic gains with Turkey.